2021
DOI: 10.2478/msp-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of optimization techniques and nano surface coating materials on microstructure of iron-nickel-chromium alloy using wire EDM process

Abstract: This research proposes developing the new hybrid optimization techniques for getting optimized wire EDM machining parameters and analysing the performance and microstructure of hybrid treatment alloy 20 material (high-velocity oxygen fuel spraying and plasma nitriding on iron-nickel-chromium alloy) after machining in wire EDM. The devising optimization is carried out using back-propagation neural networks (BPNN) integrated with fuzzy logic techniques. Taguchi L27 method uses optimized parameters in 3 factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The effect of duty cycle on wear and corrosion of Ni-B-TiN composite coatings and found that the wear resistance of the coatings improved with increasing duty cycle [14]. Selvabharathi et al (2021) reported the in uence of optimisation techniques and nano surface coating materials on microstructure of iron-nickel-chromium alloy using wire EDM process and found that the coating hardness and wear resistance improved with nano surface coating materials [15]. Mousaa et al (2021) prepared high-performance coating lms based on urethane acrylate oligomer and liquid silicone rubber for corrosion protection of mild steel and found that the coating hardness and wear resistance improved with increasing urethane acrylate oligomer concentration [16].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of duty cycle on wear and corrosion of Ni-B-TiN composite coatings and found that the wear resistance of the coatings improved with increasing duty cycle [14]. Selvabharathi et al (2021) reported the in uence of optimisation techniques and nano surface coating materials on microstructure of iron-nickel-chromium alloy using wire EDM process and found that the coating hardness and wear resistance improved with nano surface coating materials [15]. Mousaa et al (2021) prepared high-performance coating lms based on urethane acrylate oligomer and liquid silicone rubber for corrosion protection of mild steel and found that the coating hardness and wear resistance improved with increasing urethane acrylate oligomer concentration [16].…”
Section: Introductionmentioning
confidence: 99%